Bariatric Surgery: A pathway to fertility in obese – A case study - Moly K T (International Journal of Psychosocial Rehabilitation, 2020)
There is an increasing popularity of bariatric surgery in reproductive-age women. This is a description of a morbidly obese woman with polycystic ovary syndrome (PCOS) and hypothyroidism seeking treatment to become pregnant underwent Laparoscopic Sleeve Gastrectomy (LSG). The patient feels she could not achieve her wishes because of her obesity in childhood. The article explains the positive and negative experiences the woman had to undergo striving for control and normality post surgically, throughout the pregnancy and postnatal period. Immediately after the surgery her weight was 56 kg which means she has lost approximately 37 kg weight. But her present weight is 65 kg. Over a period of three years there is a gain of 9kg in the weight. The overall score of SF – 36 was 87% with the MCS higher (92% ) than PCS (83.3%). Coping with the food especially during the initial years, concerns about pregnancy and the growth of the baby often due to food intolerances were expressed. Finally the enjoyment that has come as a result of improvement in self esteem, independence in the patient, in her work and family was evident as she thinks she has taken the right decision at the right time. The present concern for her is the weight regain and struggle to maintain the new weight. The case study highlights the improvement in quality of life, at the same time reinforces the need for interventions and support groups to alleviate the concerns related to weight regain and maintenance.